Kritik Taufik Al-Hakim Atas Masyarakat Modern dalam Cerpen Daulatul Ashafir Persepektif Semiotika Umberto Eco: Taufik Al-Hakim's Criticism of Modern Society in The Story of Daulatul Ashafir's Semiotics Perspective Umberto Eco - Sholih, Mohammad Badrus (Kibas Cenderawasih, 2022)
This research is motivated by the social conditions of modern society who have lost their identity. Reproduction of signs is done to fulfill their desire to reach a point of freedom that they expect, regardless of the background of the sign present. The short story “Daulatul Ashafir” by Taufik Al-Hakim which tells about the lives of two birds and a man who are filled with the hustle and bustle of social conflicts that are relevant to the state of modern society today. This study uses Umberto Eco's semiotic theory as a theoretical basis to find signs in the text that indicate an author's criticism of modern society. The results found in this paper are some of Taufik Al-Hakim's criticisms of modern society in the form of criticisms of arrogance, consumerism, greed, and ignorance that are intertwined in the soul of modern society. The author is able to convey his criticism of modern society in the short story "Daulatul Ashafir" by placing two birds as the main character and anti-thesis against humans who are considered the highest entities of creatures in the universe by negating the life that exists outside them.